"Ngopi Fancy as a Social Representation" A Phenomenological Study of Ngopi Fancy Posts on Instagram - Halla Sayyidah Muflichah; Nurfian Yudhistira (POPULIKA, 2025)
The phenomenon of ngopi fancy coffee among young urban Indonesians has evolved into a social practice encompassing identity, status, and lifestyle representations. This study aims to uncover the subjective meaning of the ngopi fancy coffee experience as part of the construction of social identity shaped through popular culture and digital media. Using a qualitative approach with an interpretive phenomenological analysis (IPA) study design, data were collected through in-depth interviews with five urban middle-class Generation Z participants who are active on social media. The results show that ngopi fancy coffee is interpreted as a form of self-expression, achieving social validation, and a manifestation of aesthetic values in everyday life. This activity functions as a consumption practice and a means of identity performance in the digital space. Social media, especially Instagram, has become the primary medium reinforcing this identity construction by visualizing a modern, aesthetic, and exclusive urban lifestyle. This study concludes that ngopi fancy coffee reflects the relationship between popular culture, symbolic consumption, and digital identity performativity in contemporary urban society. These findings provide a theoretical contribution to the study of cultural communication and identity and a critical reflection on the capitalization of social space in the digital media era. Keywords: Fancy Coffee; Popular Culture; Phenomenology; Representation.